ANALISIS MANAJEMEN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) HIPERTENSI DI KLINIK PRATAMA DINAYLA UTAMA 84 - administrator administrator; Rr Ratna Budi Sri Sugiastuti; Gurendro Putro (Jurnal Manajerial Bisnis, 2019)
This study aims to analyze pro-hypertension management in the Primary Dinayla Utama 84 clinic for thesuccess of the prolanis program. This research method is a case study with qualitative descriptive. Researchlocation at Pratama Clinic Utama Dinayla 84 Surabaya East Java. Research data uses interviews andanalysis. The number of informants was 14 informants. Data analysis using interactive analysis. Theresults showed that hypertension prokeris management with prolanist activities was home visits andprogram participants who still did not find the indicator of success of Prolanis, namely 75% of participantsregistered and to overcome the activeness of the Pratayla Utama 84 Clinical Clinic officers.Keywords: management, prolanis, hypertension